Enhancing the market access of farmer groups in Mai Son District, Son La Province, Vietnam, through marketing and sales training, and a livestock production and trade alliance - Thinh, Nguyen Thi; Thanh, Lo Quang; Le, Pham Thi; Bravo, Aura; Burkart, Stefan (International Livestock Research Institute, 2024)
Sine 2023, the CGIAR Initiative on Sustainable Animal Productivity (SAPLING) has been fostering sustainable livestock practices in eight farmer groups (FGs) in the Mai Son District of Son La Province, Vietnam. The project has provided technical support technical support to participants to adopt advanced practices in breeding selection, animal health management, and feed and forage management. It has also enhanced the management skills of these groups by groups by defining clear roles for members and management teams, resulting in more efficient and organized operations.